Causal Uncertainty - Weinrib, Ernest J (Oxford Journal of Legal Studies, 2016)
This article examines, from the standpoint of corrective justice, three basic situations of causal uncertainty in the law of negligence. In the first situation the uncertainty is about which of the possible defendants wrongfully caused the injury. In the second situation the uncertainty is whether the injury resulted from the innocent or the wrongful aspect of the defendant’s activity. In the third situation the uncertainty is whether the defendant’s negligence failed to prevent the materialisation of an independently existing risk. In viewing the parties as the doer and the sufferer of the same injustice, corrective justice confirms the centrality of causation to negligence liability. The article shows, nonetheless, how these three situations of uncertainty can be resolved within the corrective justice framework. Moreover, what emerges from the corrective justice analysis is that causal uncertainty is not a homogeneous problem; its solution varies with the kind of situation in which the uncertainty appears.